Death After Jail Release: Matching to Improve Care Delivery. (January 2017) - Alex, Byron; Weiss, David B.; Kaba, Fatos; Rosner, Zachary; Lee, David; Lim, Sungwoo; Venters, Homer; MacDonald, Ross
The period immediately after release from prison or jail carries increased mortality risk. This study sought to better understand postrelease death by matching electronic health records from those incarcerated in New York City jails between 2011 and 2012 with vital statistics records. The in-jail and 6-week postrelease mortality rates were estimated to be 1.39 and 5.89 per 1, 000 person-years, respectively. Of 59 deaths occurring within 6 weeks of release from jail, the causes included opioid overdose (37.3%), other drugs (8.5%), chronic disease (25.4%), assaultive trauma (20.3%), and other trauma (8.5%). These data confirm that overdose death accounts for the most frequent cause of postrelease death. Matching between correctional health systems and vital statistics can inform quality improvement efforts in jail health care delivery.